Bimbingan Membaca Shalawat pada Anak Usia Dini di Desa Banyunning Geger Bangkalan - Sama'un Sama'un; Ahmad Bahrudin; Ach. Ghufron (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
Children are the next generation of the nation. Therefore they must receive serious attention and education from an early age. Early childhood is a child who is zero years old or from birth to approximately eight years old. At this age is a period that greatly influences the next stage. However, whether we are aware of it or not, today many parents feed their children too much on their formal education. Many are not aware of the benefits of learning spirituality as a support in forming moral character in children. Guidance that is practical to use without the need to add to the burden on children's minds, namely by getting used to starting or ending activities by reciting blessings. So that they feel peace of mind and always remember and can bring up a sense of love for the Messenger of Allah from an early age.